Medical Abortion Provision by Pharmacies and Drug Sellers in Low‐ and Middle‐Income Countries: A Systematic Review. Issue 1 (6th March 2018) - Footman, Katharine; Keenan, Katherine; Reiss, Kate; Reichwein, Barbara; Biswas, Pritha; Church, Kathryn
Abstract: We undertook a systematic review to assess 1) the level and quality of pharmacy and drug shop provision of medical abortion (MA) in low‐ and middle‐income countries (LMICs) and 2) interventions to improve quality of provision. We used standardized terms to search six databases for peer‐reviewed and grey literature. We double‐extracted data using a standardized template, and double‐graded studies for methodological quality. We identified 22 studies from 16 countries reporting on level and quality of MA provision through pharmacies and drug sellers, and three intervention studies. Despite widespread awareness and provision of MA drugs, even in legally restricted contexts, most studies found that pharmacy workers and drug sellers had poor knowledge of effective regimens. Evidence on interventions to improve pharmacy and drug shop provision of MA was limited and generally low quality, but indicated that training could be effective in improving knowledge. Programmatic attention should focus on the development and rigorous evaluation of innovative interventions to improve women's access to information about MA self‐management in low‐and middle‐income countries.